Exosomes and microRNAs as mediators of the exercise - Haoyuan Li; Guifang Liu; Bing Wang; Mohammad Reza Momeni (European Journal of Medical Research, 2025)
Abstract MicroRNAs (miRNAs), also known as microribonucleic acids, are small molecules found in specific tissues that are essential for maintaining proper control of genes and cellular processes. Environmental factors, such as physical exercise, can modulate miRNA expression and induce targeted changes in gene transcription. This article presents an overview of the present knowledge on the principal miRNAs influenced by physical activity in different tissues and bodily fluids. Numerous research projects have emphasized the significant impact of miRNAs on controlling biological changes brought about by physical activity. These molecules play main roles in important processes such as the growth of skeletal muscle and heart muscle cells, the creation of mitochondria, the development of the vascular system, and the regulation of metabolism. Studies have shown that physical exertion utilizes the contributions of miR-1, miR-133, miR-206, miR-208, and miR-486 to revitalize and restore skeletal muscle tissue. Moreover, detecting alterations in miRNA levels and connecting them to the specific outcomes of various exercise routines and intensities can act as indicators for physical adaptation and the reaction to physical activity in long-term diseases. Numerous studies have confirmed that extracellular vesicles (EVs) which composed of different members such as exosomes have the ability to reduce inflammation through the activation of the nuclear factor kappa B (NF-κB pathway. Furthermore, physical activity greatly affects the levels of specific miRNAs present in exosomes derived from skeletal muscle. Therefore, exosomal miRNAs target some pathways that are related to growth and development, such asWnt/β-catenin, PI3K/AKT, and insulin-like growth factor 1 (IGF1). Exercise-induced exosomes have also been identified as important mediators in promoting beneficial effects throughout the body. The aim of this review is to summarize the effect of exercise on the function of miRNAs and exosomes.